Cervical cancer with a rare umbilical metastases in prior surgical site. (2015) - Kharod, Shivam; Yeung, Anamaria; Fredenburg, Kristianna; Greenwalt, Julie
Highlights: We describe the case of an unusual port-site cervical cancer metastasis. We perform a review of the current published literature of port-site metastases. We demonstrate that our patient's case is unlike others previously described. Abstract: Introduction: Port-site metastasis of cervical cancer is a relatively rare occurrence, and has been reported in the published literature as a pre-terminal event. Presentation of case: We present the case of a 52-year-old female who was diagnosed with cervical cancer after presenting to our institution's hospital with urinary symptoms not relieved by multiple treatments with antibiotics. To fully evaluate the extent of disease, positron emission tomography-computed tomography imaging was obtained, showing an area of mildly increased fluorodeoxyglucose uptake in her umbilicus. While undergoing external-beam radiotherapy treatment for her cervical cancer, she began to experience pain in the umbilicus associated with a mass. A biopsy was taken, revealing metastatic cervical cancer at the site of a previous port-site incision for a cholecystectomy that the patient underwent 18 months before the finding. Discussion: Port-site metastasis have been reported following kidney, bladder, and colon cancer resections, with reports of cervical cancer cases being exceedingly rare. Several hypotheses have emerged as potential explanations for port-site metastasis. Conclusion: To our knowledge, this represents the first reported case of a port-site metastasis to an incision site created for an unrelated laparoscopic surgery, performed well in advance of the diagnosis of cervical cancer.